Butterfly effect in low-cycle fatigue: Importance of microscopic damage mechanism. (November 2017) - Shao, C.W.; Zhang, P.; Zhang, Z.J.; Zhang, Z.F.
Abstract: We report that materials with similar tensile properties can also exhibit quite different low-cycle fatigue (LCF) performances. Experimental results demonstrate that the LCF properties of twinning induced plasticity (TWIP) steels are naturally dominated by microscopic deformation mechanisms (mainly dislocation slip mode), which slightly influences the initial work hardening. However, such slight difference in the initial work hardening (the butterfly effect), corresponding to different damage mechanisms, accumulates and enlarges cycle by cycle during fatigue, finally leading to wide variations in cyclic stress response and fatigue life. Graphical abstract: A slight variation in monotonic flow stress may finally cause a big difference in the LCF performance of the twinning induced plasticity (TWIP) steel, which has its origin from the different dislocation slip modes.